Synthesis and crystal structure of polybis-(3-nitro-2,4-pentanediono)-copper(II), [Cu(NO2-acac)2]n - Ghali, Najat Lauibi; Al-Assadi, Mohammed Jassim; Al-Lami, Hadi Salman; Kadhum, Abdul Amir Hassan (European Journal of Chemistry, 2017)
The organo-inorganic polymer, poly[Cu(NO2-acac)23]n, has been prepared and its crystal structure was determined. The structure consists of a trimeric unit in which, acetylacetone ligated symmetrically to copper atoms that pose in the center of octahedrons. The three octahedral fragments of the trimer are linked to each other through nitro group. Crystal Data: C10H12CuN2O8, Mr = 351.76, triclinic, P-1 (No. 2), a = 5.8237(2) Å, b = 7.7963(3) Å, c = 7.8847(3) Å, α = 81.988(2)°, b = 75.294(2)°, γ = 72.217(2)°, V = 328.98(2) Å3, T = 143(2) K, Z = 1, Z’ = 0.5, μ(Mo Kα) = 1.703, 3021 reflections measured, 1421 unique (Rint = 0.0156) which were used in all calculations. The final wR2 was 0.0686 (all data) and R1 was 0.0217 (I > 2σ (I)).